Surveying the forest: A meta‐analysis, moderator investigation, and future‐oriented discussion of the antecedents of voluntary employee turnover. Issue 1 (30th March 2017) - Rubenstein, Alex L.; Eberly, Marion B.; Lee, Thomas W.; Mitchell, Terence R.
Abstract: Recent narrative reviews (e.g., Hom, Mitchell, Lee, and Griffeth, 2012; Hom, Lee, Shaw, and Hausknecht, 2017) advise that it is timely to assess the progress made in research on voluntary employee turnover so as to guide future work. To provide this assessment, we employed a three‐step approach. First, we conducted a comprehensive meta‐analysis of turnover predictors, updating existing effect sizes and examining multiple new antecedents. Second, guided by theory, we developed and tested a set of substantive moderators, considering factors that might exacerbate or mitigate zero‐order meta‐analytic effects. Third, we examined the holistic pattern of results in order to highlight the most pressing needs for future turnover research. The results of Step 1 reveal multiple newer predictors and updated effect sizes of more traditional predictors, which have received substantially greater study. The results of Step 2 provide insight into the context‐dependent nature of many antecedent–turnover relationships. In Step 3, our discussion takes a bird's‐eye view of the turnover "forest" and considers the theoretical and practical implications of the results. We offer several research recommendations that break from the traditional turnover paradigm, as a means of guiding future study.